1982
DOI: 10.1007/bf00313727
|View full text |Cite
|
Sign up to set email alerts
|

Adult onset centronuclear myopathy with peripheral nerve involvement

Abstract: A case of centronuclear myopathy is presented, showing a rapid course in a 47-year-old male. Clinical and muscular findings were consistent with the diagnosis of centronuclear myopathy. On nerve biopsy, there was evidence of a regenerative process. Electron microscopy showed proliferation of Schwann cells with numerous Büngner's bands and other anomalies. This rare case with peripheral nerve changes may provide evidence to support the hypothesis of peripheral nerve involvement in centronuclear myopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…When using 2,2 0dithiodibenzoic acid ester diol as the alternative part of BDO as a chain extender, the length of the hard segment in the polyurethane molecular main chains are uneven, and the molecular interactions forces such as hydrogen-bonding interactions in the hard segment is weakened, resulting in reduced mechanical properties. 39 Consequently, the mechanical properties of SFPU-A synthesized with Diol-S-A as a chain extender were notably inferior to those of SFPU-D synthesized with Diol-S-A as a soft segment used in the prepolymer reaction.…”
Section: Mechanical Property Analysismentioning
confidence: 97%
“…When using 2,2 0dithiodibenzoic acid ester diol as the alternative part of BDO as a chain extender, the length of the hard segment in the polyurethane molecular main chains are uneven, and the molecular interactions forces such as hydrogen-bonding interactions in the hard segment is weakened, resulting in reduced mechanical properties. 39 Consequently, the mechanical properties of SFPU-A synthesized with Diol-S-A as a chain extender were notably inferior to those of SFPU-D synthesized with Diol-S-A as a soft segment used in the prepolymer reaction.…”
Section: Mechanical Property Analysismentioning
confidence: 97%
“…Although CNM is intrinsically a muscle disorder, some clinical reports have shown that the peripheral nervous system is also affected in the disease (Mouren et al . ). In 2007, Echaniz‐Laguna and co‐workers observed a deficient peripheral nerve conduction in CNM‐patients harboring the dynamin‐2 middle‐domain mutation E368Q (Echaniz‐Laguna et al .…”
Section: Dynamin‐2 Mutations In Centronuclear Myopathy Associated Witmentioning
confidence: 97%